PEER CONFORMITY: A GATEWAY TO SELF-HARM BEHAVIOR IN SCHOOL STUDENTS? - Fitri, Laila Magfirah; Juliawati, Dosi; Yandri, Hengki (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Self-harm behavior has become a significant mental health problem among adolescents. This study aimed to examine the relationship between peer conformity and self-harm tendencies in school students. A descriptive correlational quantitative research method was used involving 234 tenth and eleventh grade students. Data were collected using a peer conformity scale and a self-harm scale that had been tested for validity and reliability. Non-parametric correlation analysis showed a negative relationship between the two variables. Students who self-harmed less tended to have higher levels of conformity. This finding indicates that peer conformity can be a protective factor against self-harm behavior. However, excessive conformity can also have a negative impact if group norms are unhealthy. Further research is recommended to investigate the influence of peer pressure on self-harm and develop more comprehensive interventions to prevent this behavior.